Erythropoietin Receptor/β Common Receptor: A Shining Light on Acute Kidney Injury Induced by Ischemia-Reperfusion - Wu, Yuanyuan; Yang, Bin (Frontiers in Immunology, 2021)
Acute kidney injury (AKI) is a health problem worldwide, but there is a lack of early diagnostic biomarkers and target-specific treatments. Ischemia-reperfusion (IR), a major cause of AKI, not only induces kidney injury, but also stimulates the self-defense system including innate immune responses to limit injury. One of these responses is the production of erythropoietin (EPO) by adjacent normal tissue, which is simultaneously triggered, but behind the action of its receptors, either by the homodimer EPO receptor (EPOR)2 mainly involved in erythropoiesis or the heterodimer EPOR/β common receptor (EPOR/βcR) which has a broad range of biological protections. EPOR/βcR is expressed in several cell types including tubular epithelial cells at low levels or absent in normal kidneys, but is swiftly upregulated by hypoxia and inflammation and also translocated to cellular membrane post IR. EPOR/βcR mediates anti-apoptosis, anti-inflammation, pro-regeneration, and remodeling via the PI3K/Akt, STAT3, and MAPK signaling pathways in AKI. However, the precise roles of EPOR/βcR in the pathogenesis and progression of AKI have not been well defined, and its potential as an earlier biomarker for AKI diagnosis and monitoring repair or chronic progression requires further investigation. Here, we review biological functions and mechanistic signaling pathways of EPOR/βcR in AKI, and discuss its potential clinical applications as a biomarker for effective diagnosis and predicting prognosis, as well as directing cell target drug delivery.